Tendência da sífilis congênita no estado do Pará até 2025 - SALGUEIRO, Suzana Aparecida Lobato (Universidade Federal do Pará, 2017)
Syphilis is an infectious disease caused by the bacterium Treponema pallidum (T. pallidum) and still stands today as one of the biggest challenges to public health. According to the World Health Organization (WHO), about 937,000 people are infected, and 10 to 15% of these individuals would be pregnant women, with 70% chance of transmitting the parasite to their concepts, for lack of proper treatment. The objective of this descriptive study, ecological and retrospective, was to analyze the epidemiology of congenital syphilis and maternal syphilis in the state of Para mesoregions in the period 2006-2015 and trend analysis by 2025. In the methodology we used data relating to cases of congenital syphilis and maternal syphilis, using as a primary source of information available in the State Coordination of STD / AIDS, the State Public Health Department (SESPA), Pará state, which receives the SINAN data, diagnosed between 2006-2015 in the state of Pará municipalities, adopting the mesoregions criteria of integration, the total of twelve. The variables were sociodemographic and epidemiological order of newborns and mothers with syphilis, descriptive statistical tests being applied, using the G and chi-square test and the Student t test and Mann-Whitney. For trend analysis were used polynomial regression models for time series. It was considered the 95% confidence interval with significant p-value <0.05. This study met the criteria of Resolution 466/2012 CONEP. It was observed in this study an increased incidence of congenital syphilis in the state of Para 0.4 mesoregions in 2006 to 46.0 cases / 10,000 live births in 2013. In trend analysis by the year 2025. The results observed an estimate High of cases in most of the state of Para mesoregions, especially in the Tapajos, Rio Carajás and grass; and low in the Araguaia and Marajó. Regarding RN's was not observed significant difference in sex, but there was a predominance of mulattos. As for the mothers, prevailed the age group between 20-34 years and also the brown race, most mothers held prenatal care and the treatment was performed, but mostly inappropriately. Found an increase in the incidence of congenital syphilis in mesoregions the 2006-2013 state of Pará; the mesoregions with greater growth trends by 2025 are Tapajos, Rio Carajás and grass; the period 2006-2015 the frequency of genres of RN's was similar, the race of frequent neonates was mixed; from 2007 to 2015 maternal age group that predominated was between 20 and 34 years in all mesoregions and congenital syphilis occurred more frequently in mothers enrolled in prenatal care, but with high frequency of inadequacy to the treatment.